Les moyens de manifestation de l’ironie dans les discours humoristiques - Abdelssadok Hachimiya (My University, 2012)
Our work is an analysis of two corpuses, consisting ironic texts, excerpts from performances of two comedians French: Anne Roumanoff and Florence Foresti. Through this paper, we try to realize the irony as a phenomenon through a polyphonic approach. We draw on work dAnscombre and Ducrot, and especially the theory of Haillet on this concept. We note statements, interpreted as ironic, we put them in relation to various discursive environments to detect the implicit views that are, or not paid by the original speaker, but expressed implicitly and / or carried by enunciators. Then we discuss some discursive strategies used in these speeches, and other means of manifestation of irony as gestures or mime.